2010
DOI: 10.1007/s10753-010-9237-9
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Physical Training on the Cardio-Inflammatory Disorder Induced by Lung Ischemia/Reperfusion in Rats

Abstract: Our laboratory demonstrated that training program attenuated the inflammatory responses in lung ischemia/reperfusion (IR). Considering the importance of the inflammatory responses on the cardiovascular system, we evaluate the effect of physical training on the vascular responsiveness and its underlying mechanism after lung IR. Male Wistar rats were submitted to run training and lung IR. Concentration-response curves for relaxing and contracting agents were obtained. Protein expressions of SOD-1 and p47(phox), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Considering the relevance of exercise training in preventing or improving the deleterious effects of chronic diseases such as dyslipidemia and atherosclerosis, our data support our hypothesis that eNOS polymorphism at position -786T>C and Intron 4b/a interferes with the beneficial effects of 8 weeks of exercise training on cardiometabolic diseases in postmenopausal women. Regarding oxidative stress status, our data confirm previous results from our laboratory using an experimental model (29,30) showing that aerobic exercise promotes an improvement of antioxidant status by increasing plasma SOD levels, which in turn can ameliorate vascular and metabolic functions. In contrast, no change was found in thiobarbituric acid-reactive species concentrations in plasma measured as MDA in this particular population, showing that 8 weeks of exercise training did not modify the oxidant status.…”
Section: Discussionsupporting
confidence: 89%
“…Considering the relevance of exercise training in preventing or improving the deleterious effects of chronic diseases such as dyslipidemia and atherosclerosis, our data support our hypothesis that eNOS polymorphism at position -786T>C and Intron 4b/a interferes with the beneficial effects of 8 weeks of exercise training on cardiometabolic diseases in postmenopausal women. Regarding oxidative stress status, our data confirm previous results from our laboratory using an experimental model (29,30) showing that aerobic exercise promotes an improvement of antioxidant status by increasing plasma SOD levels, which in turn can ameliorate vascular and metabolic functions. In contrast, no change was found in thiobarbituric acid-reactive species concentrations in plasma measured as MDA in this particular population, showing that 8 weeks of exercise training did not modify the oxidant status.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, we found that the protein expression of the NADPH oxidase subunit p47 phox was higher in SRT rats, whereas aerobic exercise training was effective in normalizing p47 phox expression. Physical training performed prior to lung ischemia/reperfusion has been reported to be effective in normalizing p47 phox protein expression in mesenteric arteries [41] . p47 phox plays an important role in superoxide production in response to AngII [42] .…”
Section: Discussionmentioning
confidence: 99%